ANALISIS POTENSI SEKTOR PERIKANAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MIMIKA - Apriani Samaa; Fefridayanti Palino; Yahya Nusa (BORJUIS: JURNAL OF ECONOMY, 2024)
The aim of the research is to analyze the potential of the fisheries sector for Regional Original Income and its potential contribution. The method used in this research is the descriptive method, using a quantitative approach which has the aim of analyzing social events, phenomena or conditions. The descriptive research method is fact finding using correct interpretation. The results of this research show that the potential for levies from the Mimika Regency Fisheries Service will get greater results in several subsectors than the realization of the Mimika Regency Fisheries Service in 2022, namely on the use of regional wealth which has a potential of IDR 1,940,400,000 from the previous realization of IDR 497,315,000 , on sales of ice blocks which have a potential of IDR 84,000,000 from the previous realization of IDR 77,000,000, and on fishing business permits which have a potential of IDR 67,500,000 from the previous realization of IDR 61,677,759. This positive potential has not yet shown a significant contribution to local original income, so the average contribution during 2020-2023 is very low. If the management of the fisheries sector is handled well, it will increase Mimika's PAD and of course it can be used to support infrastructure development, public services and other development programs.